IMPLEMENTASI PEMBELAJARAN PR0BLEM BASED LEARNING PADA MATA PELAJARAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN LANDUNGSARI 1 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve student learning outcomes through the implementation of the Problem Based Learning (PBL) method in the Pancasila Education subject, focusing on the material of Pancasila values for Grade VB elementary school students. Based on preliminary observations, students faced difficulties in understanding the material due to teacher-centered learning, limited active student involvement, and a classroom atmosphere that tended to be passive.This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects consisted of 22 Grade VB students at SDN Landungsari 1 in the even semester of the 2026 academic year. Data collection techniques included observation, learning outcome tests, and documentation using instruments such as observation sheets of teacher and student activities and evaluation questions. The data were analyzed using descriptive quantitative methods.The results showed an improvement in student learning outcomes, with the average initial score of 65.00 and a completeness rate of 45.45%, which increased to 72.27 (63.64%) in cycle I and reached 84.55 (90.91%) in cycle II. In addition, learning activities also showed positive changes, with students becoming more active and teachers more effective in facilitating the learning process.